PREGNANCY PROTEINS: EARLY INDICATION OF PREGNANCY DIAGNOSIS IN FARM ANIMALS: Life Science-Veterinary Science - NANDRE, RAHUL; JOSHI, CHAITANYA; DERASHRI, HARESH (International Journal of Life Science and Pharma Research, 2012)
During gestation, many important molecular factors associated with embryo implantation and development occur within the female reproductive tract. The endometrium includes the muscosal lining of the uterus, which gives a convenient location for implantation and development of a fertilized egg and fetus. At present, the molecular cascades in the uterus endometrium during pregnancy periods in farm animals have not been elaborated completely. Many pregnancy proteins were expressed in the uterus endometrium during pregnancy. The expressions of these proteins involved in endometrium function and endometrium development from early to late gestation are associated with the regulation of endometrium development for maintaining pregnancy. The pregnancy proteins have key roles in tissue morphogenesis and growth. Growth promoters. Early pregnancy factor, Interferon, prolactin and Pregnancy associated Glycoproteins. Potential roles for pregnancy proteins have been identified in placental development and function, fetal growth, immunoregulation of pregnancy, embryo implantation and placental development. It is also necessary to consider the mechanisms controlling pregnancy from protein expression. This review focuses on pregnancy proteins as indication for early pregnancy diagnosis to highlight prospects for future research.